Dynamics of Middle Classes: Between Expansion and Uncertainty Russian-French Scientific Conference, NRU HSE, Moscow, October 3rd, 2019 - Elena Nazarbaeva (Journal of Economic Sociology, 2019)
The conference “Dynamics of Middle Classes: Between Expansion and Uncertainty” was conducted at NRU HSE. The conference was devoted to stratification issues in general and the middle class in particular. The conference was organized by the Institute for Social Policy NRU HSE and the French Embassy in Russia.The topic of the middle class has been popular for a long time, but there is still no unique definition for this notion. The participants in the conference managed to touch upon three levels of work in terms of “the middle class”: theory, methodology, and empirical studies. Regarding the theory of the middle class, the presenters mentioned that economic and sociological theories exist and are described in their main theoretical models. The analysis of different papers devoted to the middle class provides the ability to show diversity at a methodological level, including the diversity of criteria used for middle class identification. Nevertheless, the common idea for most of the approaches is the idea of object complexity and the necessity to combine several characteristics to identify the middle class. Appealing to empirical studies of the middle class in Russia and France showed that in both countries, the middle class is not homogenous, and it is better to use the term “middle classes.” In Russia, the middle class has relatively high levels of well-being but is not autonomous from the state. However, it does not feel that social protection is critical due to existing inequalities and a lack of stability in society.